Sex pilus specific bacteriophage to drive bacterial population towards antibiotic sensitivity - Colom, Joan; Batista, Diego [UNESP]; Baig, Abiyad; Tang, Ying; Liu, Siyang; Yuan, Fangzhong; Belkhiri, Aouatif; Marcelino, Lucas [UNESP]; Barbosa, Fernanda [UNESP]; Rubio, Marcela [UNESP]; Atterbury, Robert; Berchieri, Angelo [UNESP]; et al. (Springer Nature, 2019)
Antimicrobial resistance (AMR) is now a major global problem largely resulting from the overuse of antibiotics in humans and livestock. In some AMR bacteria, resistance is encoded by conjugative plasmids expressing sex-pili that can readily spread resistance through bacterial populations. The aim of this study was to use sex pilus-specific (SPS) phage to reduce the carriage of AMR plasmids. Here, we demonstrate that SPS phage can kill AMR Escherichia coli and select for AMR plasmid loss in vitro. For the first time, we also demonstrate that SPS phage can both prevent the spread of AMR Salmonella Enteritidis infection in chickens and shift the bacterial population towards antibiotic sensitivity.